Essay Review: Two Perspectives on Possession. Possession and Exorcism by Hans Naegeli-Osjord, and The Devil Within by Brian P. Levack - Grosso, Michael (Journal of Scientific Exploration, 2014)
The phenomenon of possession has a long, complicated history and a dark, unsavory side. Nevertheless, it has persisted in one form or another until present times. The books under review afford two perspectives on demonic possession: psychiatric and historical. Both authors are informed in their respective fields. They are critical writers and agree on a basic factual underpinning of the controversial phenomena. The grounds for this concord lie in the recurrence of the phenomena and the cumulatively large number of recorded witnesses. Both are aware of the academic prejudice toward the alleged realities of possession. Historian Brian Levack is interested in the historical and performance dimension of the untoward effects, and plays down their ontological strangeness and implications. The Swiss psychiatrist Hans Naegeli is more concerned with these implications, for example, for psychiatry, noting the unhelpfulness of standard materialist outlooks. The books are mainly complementary and affirm the reality of some of the strangest phenomena in the history of psychophysical anomalies.